Analysis of Inverse Angle Method for Controlling Two Degree of Freedom Manipulator - Hendri Maja Saputra; Zainal Abidin; Estiko Rijanto (National Research and Innovation Agency, 2012)
Driver mechanism with two degree of freedom (MP 2-DK) is a robotic device that can be used for various applications such as turret drive system, gutling gun, launcher, radar antennas, and communications satellite antennas. The precision and the speed of a MP 2-DK are determined by its control system. The calculation inverse angle due to interference in six degree of freedom is necessary to control a MP 2 DK. This paper analyses three calculation methods of inverse angle which are iteration method using Jacobian matrix, reduction of matrix equations using positioning geometry, and an analytical derivation using a rotation matrix. The simulation results of the three methods showed that the first and the third methods could visually demonstrate three rotational disturbances, whereas the second method could only demonstrate the pitch and yaw (PY) disturbances. The third method required less processing time than the first and the second methods. The best method based on this research was the method of rotation matrix.